2015
DOI: 10.3109/10520295.2015.1019926
|View full text |Cite
|
Sign up to set email alerts
|

Adrenal response of male rats exposed to prenatal stress and early postnatal stimulation

Abstract: Stress in pregnant rats caused by chronic immobilization alters the pattern of secretion of corticosterone and modifies the hypothalamic-pituitary-adrenal axis (HPA) of the fetus. Early postnatal handling, however, may reverse the effects of increased secretion of corticosterone. We investigated the effects of prenatal stress and postnatal handling on the activity of the HPA axis of male offspring of stressed female rats. Male 90-day-old rats from four groups were investigated: prenatally stressed animals with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 30 publications
1
6
0
1
Order By: Relevance
“…The current findings are consistent with those of Campeau et al (2010), in which exercise animals displayed blunted ACTH and corticosterone responses to an acute novel environment compared to sedentary animals. Prairie voles in the exercise group also had a significantly smaller adrenal weight to body weight ratio, compared to the sedentary condition, suggesting that exercise can protect against enlarged adrenal glands, which has been observed previously in chronically stressed animals (Kim et al, 2008; Liaudat et al, 2015). Taken together, the current findings indicate that voluntary physical activity attenuates both acute and chronic endocrine stress responses.…”
Section: Discussionsupporting
confidence: 76%
“…The current findings are consistent with those of Campeau et al (2010), in which exercise animals displayed blunted ACTH and corticosterone responses to an acute novel environment compared to sedentary animals. Prairie voles in the exercise group also had a significantly smaller adrenal weight to body weight ratio, compared to the sedentary condition, suggesting that exercise can protect against enlarged adrenal glands, which has been observed previously in chronically stressed animals (Kim et al, 2008; Liaudat et al, 2015). Taken together, the current findings indicate that voluntary physical activity attenuates both acute and chronic endocrine stress responses.…”
Section: Discussionsupporting
confidence: 76%
“…These ELS-induced alterations in corticosterone plasma levels could obviously be caused by the earlier mentioned alterations in CRH and ACTH release, but could also be attributed to abnormal function of the adrenal gland itself, as increases in adrenal weight and cortex-to-medulla ratio have been reported as a consequence of PS (Ward et al, 2000; Fan et al, 2009; Liaudat et al, 2015). However, the frequent inconsistencies in findings emphasize the extremely complex modulatory effects ELS exerts on the HPA-axis, depending on the precise developmental stage affected, the exact stressor used (its frequency, duration, etc.…”
Section: Hpa-axis Programming By Early Life Stress (Els)mentioning
confidence: 95%
“…To study the effects of prenatal stress (PS) exposure on the offspring, dams are most frequently stressed by physical restraint (Lemaire et al, 2000; Mandyam et al, 2008; Belnoue et al, 2013; de Souza et al, 2013; Madhyastha et al, 2013; Xu et al, 2014) or immobilization of the limbs (Liaudat et al, 2015), often for multiple times a day. Alternatively, exposure to foot shocks (Estanislau and Morato, 2005, 2006), hypoxia (Fan et al, 2009; Wang X. et al, 2013), or multiple variable stressors over the course of multiple days (Lee et al, 2007; Fan et al, 2009; Zohar and Weinstock, 2011) are applied.…”
Section: Hpa-axis Programming By Early Life Stress (Els)mentioning
confidence: 99%
“…59 Another possible mechanism involved in the disruption of corticosterone levels observed in prenatally stressed rats was the altered parameters of adrenal gland physiology. As Liaudat et al 61 showed, the cortex:medulla ratio, apoptotic index and caspase 3 expression of adrenal gland returned to control levels when the prenatally stress animals were handled. Figure 1 shows the timeline of experimental events in a research model aimed to evaluate the effects of prenatal stress and PS on endocrine and immune systems.…”
Section: Effect Of Postnatal Early Stimulations On Hypothalamic-pituimentioning
confidence: 89%